Self-Defense and Police Reporting of Intimate Partner Violent Victimization: A Comparison of White, Black, and Hispanic Women Victims - Powers, Ráchael A. (Journal of interpersonal violence, 2023)
Although the use of self-defense is common in incidents of intimate partner violence (IPV), correlates of self-protective behaviors in IPV are less known. Furthermore, while research has examined the unintended consequence of dual arrest as a result of using self-defense in IPV incidents, research has not examined whether self-defense is associated with the likelihood of reporting the victimization to the police. The purpose of this study is to first examine the racial differences in the use of self-defense in incidents of IPV. Second, this study examines the relationship between the use of physical self-defense and formal help-seeking (i.e., calling the police) and whether those relationships vary across race/ethnicity for White, Black, and Hispanic women. Using a large nationally representative sample of IPV incidents in the United States, this study found that incidents with Black female victims were more likely to feature physical self-defense compared to incidents with White female victims. Furthermore, incidents with Black female victims were more likely to be reported to the police. There was a positive relationship between physical self-defense and reporting to the police for Black women and an inverse relationship between physical self-defense and reporting to the police for Hispanic women.